An energy-based damage model for seismic response of steel structures. - Benavent-Climent, A.
This paper proposes a new model for quantifying the damage in structural steel components subjected to randomly applied flexural/shear stress reversals, such those induced by earthquakes. In contrast to existing approaches that consider the damage as a combination of the global amount of dissipated energy and maximum displacement, the proposed model represents the damage by two parameters: (a) the total dissipated energy and (b) the portion of the energy consumed in the skeleton part of the load?displacement curve. These parameters are employed to define a single ?damage index?, which measures the level between 0 (no damage) and 1 (failure). The proposed model takes into account that the ultimate energy dissipation capacity of the steel component is path-dependent and can change throughout the entire response duration. The new model is derived from low-cycle fatigue static tests of round steel rods and steel plates subjected to bending and shear. The accuracy of the model is verified experimentally through dynamic real-time shaking table tests. From these tests, it is observed that the proposed model measures the level of damage at any stage of the loading process reasonably well and predicts the failure of the structural component accurately. The model can be easily implemented in a computer program to assess the level of seismic damage and the closeness to failure in new structures or to evaluate the safety of existing ones.
Keywords: Structural damage characterization; Ultimate energy dissipation capacity; Steel structures